Identification of Parameters and States in PMSMs - Mercorelli, Paolo (Electronics (Basel), 2023)
This paper discusses the importance of accurately identifying the parameters and states in permanent magnet synchronous motors (PMSMs) and their impact on motor performance and efficiency. This study was conducted to demonstrate the significance of these parameters. The results showed that inaccurate identification of the friction coefficient and moment of inertia led to poor motor performance, instability, and reduced efficiency. Accurate identification of these parameters is necessary for the proper control and operation of PMSMs. This paper highlights the various methods for calculating the friction coefficient and moment of inertia, as well as their potential limitations. The findings of this study emphasize the importance of accurately identifying these parameters for the efficient and effective operation of PMSMs.